/Cloud/Watching or Portrait of a Young Artist in 1990s Kuala Lumpur - Soon, Simon (University of Chicago Press, 2018)
Simon Soon explores how Yee I-Lann and her creative community created a shared space for urban youths at a transitional moment in 1990s Kuala Lumpur.